Anatomical variation of the internal carotid artery and its implication to the endoscopic endonasal translacerum approach. Issue 5 (27th January 2021) - Umehara, Toru; Taniguchi, Masaaki; Akutsu, Nobuyuki; Kimura, Hidehito; Uozumi, Yoichi; Nakai, Tomoaki; Kishima, Haruhiko; Kohmura, Eiji
Abstract: Background: The endoscopic endonasal trans‐lacerum approach (EETLA) is useful in handling skull base tumors around inferior petrous apex (IPA); however, its surgical corridor is exclusively a triangular space (supra‐eustachian triangle [SET]), between the internal carotid artery (ICA) and eustachian tube. Methods: We investigated correlation between SET size and extent of resection around the IPA (lateral extent of resection [EOR]) through a retrospective analysis of 15 surgeries using EETLA. Results: Of 15 cases (9 chordomas, 4 chondrosarcomas, and 2 meningiomas), 20 sides of IPA were affected by the tumor. When being restricted to sides with severe lateral tumor extension beyond the midpoint of petrous ICA (10 sides), the SET size was significantly broader in the group with lateral EOR of ≥90% ( p value = 0.019). Conclusions: The SET size was a powerful index of tumor resectability in EETLA, especially in cases with severe tumor extension. The individual anatomical variations should be considered when determining EETLA application.